Spatial and temporal proteomics reveals the distinct distributions and dynamics of O-GlcNAcylated proteins - Senhan Xu; Ming Tong; Suttipong Suttapitugsakul; Ronghu Wu (Cell Reports, 2022)
Summary: Protein O-GlcNAcylation plays critical roles in many cellular events, and its dysregulation is related to multiple diseases. Integrating bioorthogonal chemistry and multiplexed proteomics, we systematically and site specifically study the distributions and dynamics of protein O-GlcNAcylation in the nucleus and the cytoplasm of human cells. The results demonstrate that O-GlcNAcylated proteins with different functions have distinct distribution patterns. The distributions vary site specifically, indicating that different glycoforms of the same protein may have different distributions. Moreover, we comprehensively analyze the dynamics of O-GlcNAcylated and non-modified proteins in these two compartments, respectively, and the half-lives of glycoproteins in different compartments are markedly different, with the median half-life in the cytoplasm being much longer. In addition, glycoproteins in the nucleus are more dramatically stabilized than those in the cytoplasm under the O-GlcNAcase inhibition. The comprehensive spatial and temporal analyses of protein O-GlcNAcylation provide valuable information and advance our understanding of this important modification.